Enhancing sustainability amongst oil palm smallholders in Malaysia. (2018) - Begum, Halima; Siwar, Chamhuri; Alam, A.S.A. Ferdous; Choy, Er Ah; Ishak, Suraiya; Alam, Lubna
Oil palm research is performed to develop new and upgraded products to face global challenges and thus, the industry is emerging as a dependable source of empowerment for the country. However, it also poses a serious threat due to unawareness of sustainability issues by the smallholders. Thus, this study assesses the actions of oil palm smallholders in a sustainable manner from the environment, economic, and social perspectives. The primary data is collected through a questionnaire survey with 50 supported smallholders in the Terengganu state under the FELDA scheme in Malaysia. The result demonstrates that dependent smallholders with primary level education are responsible for most of the pollution in the environment due to wrong agricultural practices. The study suggests that there is room for improvement in the social, environmental, and economic aspects of sustainability through intensive and quality training, depending on the role played by the authorities and the dependent smallholder cooperatives.